Overview and Comparison of PLA Filaments Commercially Available in Europe for FFF Technology - Andronov, Vladislav; Beránek, Libor; Krůta, Vojtěch; Hlavůňková, Lucie; Jeníková, Zdeňka (Polymers, 2023)
This study presents a comprehensive techno-economic analysis of PLA materials for fused filament fabrication (FFF) from eight European manufacturers. The comparison involved rigorous experimental assessments of the mechanical properties, dimensional accuracy, and print quality using standardized methods and equipment such as tensile and CT testing. What makes this study unique is the consistent methodology applied, considering factors such as material color, printing temperature, printing orientation, filament diameter, and printer selection, to ensure meaningful and reliable results. Contrary to the common belief that a higher price implies better quality, the study revealed that the second cheapest PLA material achieved the best overall performance within the methodology employed. The study also confirmed certain observations, such as the influence of printing orientation and geometry on dimensional accuracy and mechanical properties, as well as the significant disparities between manufacturer-provided values and actual measured mechanical properties, highlighting the importance of experimental verification. Hence, the findings of this study hold value not only for the scientific community but also for hobbyist printers and beginners in the 3D printing realm seeking guidance in material selection for their projects. Furthermore, the methodology employed in this research can be adapted for evaluating a broad range of other 3D printing materials.
Keywords: 3D printing; filament comparison; additive manufacturing; FDM; PLA; FFF